ANALISIS PEMBIAYAAN, TUNJANGAN DAN KESEJAHTERAAN GURU DI MADRASAH IBTIDAIYAH MIFTAHUL HUDA - M. Shafwan; Moh. Thayyib; Ramadhan, Yusfar (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
Financing in an educational institution is so important to determine the education program to run and develop. So it can be concluded that without the financing of education, education will stagnate until finally it does not operate. In an educational institution, of course, teachers are the main actors in improving human resources, teachers are also a factor that influences the success or failure of the learning process. MI Miftahul huda is the object of this research regarding financing, allowances, and teacher welfare. The qualitative method used by researchers to obtain data regarding financing, welfare, and tunjagan at MI Miftahul huda is by interviewing, collecting related documentation. The purpose of this study is to explore and analyze the sources and expenditures in the financial sector at MI Miftahul huda. With the results of the research, the source of funds obtained at MI Miftahul huda is only APBN BOS funds for financing and teacher benefits.